Managing educational sector via self-evaluation policy. Haridussüsteemi juhtimine läbi sisehindamise - Ploom, Kristi; Irs, Reelika (Estonian Discussions on Economic Policy, 2010)
Performance evaluation is not a new concept in private sector, while in public sector organisations it has been taken into use since the implementation of performance management. Evaluation is necessary to make the future-oriented management decisions based on the information available today, in order to achieve desired performance. The authors analysed self-evaluation reports prepared in Estonian general schools in 2008. Self-evaluation reports were analysed to see, if the relationships and roles, patterns of governance and accountability, flow of resources, the headmaster’s role, educational and other values in Estonian schools have hanged enough, to provide education service, which responds to the high expectations of contemporary society. Although the analyses of OECD surveys’ results show that the organising of the Estonian educational sector is a good example for many other countries, the actual situation in the schools is not as positive. There are high expectations put on schools by the policymakers’ level, but schools do not have enough ability to reach them. There is a lack of financial resources, knowledge and organisational willingness